INVESTIGATIONS OF MECHANICAL PROPERTIES AND MICROSTRUCTURE ANALYSIS OF AL 7075 GNP’S COMPOSITES - Ami Ardi, Muhamad Afiq Affandi (IRC, 2021)
Aluminium matrix composites are used frequently in the automotive, aerospace, and electronic industries because of their important performance such as high strength to weight ratio, high ductility, high corrosion strength, good electrical and thermal conductivity.